The Effect of Maternal Obesity on Oxytocin Requirements to Achieve Vaginal Delivery - Adams, April D.; Coviello, Elizabeth M.; Drassinower, Daphnie (American Journal of Perinatology, 2020)
Objective Our objective was to determine if obese women are more likely to require oxytocin rates > 20 mU/min to achieve vaginal delivery, compared with normal weight women.Study Design This is a retrospective cohort study of deliveries at the MedStar Washington Hospital Center and MedStar Georgetown University Hospital.Results There were 4,284 births included in the analysis. Thirty-three per cent of deliveries were among women classified as overweight (body mass index [BMI] 25–29.9 kg/m2) and 58% were among women classified as obese (BMI >30.0 kg/m2), 12% were classified as class III obesity (BMI >40 kg/m2). Overall 110 (2.6%) women required an oxytocin rate of >20 mU/min. Doses of oxytocin >20 mU/min for women in the overweight, class I obesity, and class II obesity groups were 2.6, 1.9, and 1.6%, respectively. Deliveries among women with class III obesity had a significantly longer duration of oxytocin exposure (10.7 hours) compared with the normal weight group (8.2 hours, p < 0.001), and had a higher maximum rate of oxytocin compared (10 mU/min) to normal weight women (8 mU/min, p < 0.001).Conclusion Obese women are more likely to require oxytocin rates more than 20 mU/min, higher doses of oxytocin, and greater duration of oxytocin exposure to achieve a vaginal delivery.
Keywords: obesity; oxytocin; labor induction; vaginal delivery